Bulk titanium–graphene nanocomposites fabricated by selective laser melting. Issue 10 (12th March 2019) - Hu, Zengrong; Wang, Dini; Chen, Changjun; Wang, Xiaonan; Chen, Xiaming; Nian, Qiong
Abstract: Abstract : In this report, bulk graphene–reinforced titanium (Ti–Gr) nanocomposite with millimeter thickness was fabricated by selective laser melting process. Demonstrated by the characterizations of scanning electron microscopy, energy dispersive spectroscopy, X-ray diffraction, X-ray photoelectron spectroscopy, and Raman spectra, graphene nanoplatelets were successfully embedded into the titanium matrix with a uniform dispersion due to a fast heating–cooling process. High-resolution transmission electron microscopy was used to investigate the interface between titanium and graphene, where a certain amount of carbide was formed attribute to the chemical reaction between them during multilayer laser melting. A high density of dislocations was observed surrounding the graphene nanoplatelets in titanium matrix. The strength and elastic modulus of the nanocomposites were significantly improved, which has been demonstrated by nano-indentation tests. The hardness of the bulk Ti–Gr nanocomposites was approximately 1.27 times higher than pristine Ti counterpart. The strengthening mechanisms were discussed in detail.